Integrate $\sin^{-1}\frac{2x}{1+x^2}$

The solution is given in my reference as: $2x\tan^{-1}x-\log(1+x^2)+C$.

But, is it a complete solution ?

My Attempt $$ \int 2\tan^{-1}x \, dx=\int \tan^{-1}x \cdot 2\,dx=\tan^{-1}x\int2\,dx-\int\frac{1}{1+x^2}\int2\,dx\cdot dx\\ =\tan^{-1}x \cdot2x-\int\frac{2x}{1+x^2}\,dx=2x\tan^{-1}x-\log(1+x^2)+C $$ $$ 2\tan^{-1}x=\begin{cases}\sin^{-1}\frac{2x}{1+x^2}\text{ if }|x|\leq{1}\\ \pi-\sin^{-1}\frac{2x}{1+x^2}\text{ if }|x|>{1}\text{ and }x>0\\ -\pi-\sin^{-1}\frac{2x}{1+x^2}\text{ if }|x|>{1}\text{ and }x<0 \end{cases}\\ \sin^{-1}\frac{2x}{1+x^2}=\begin{cases}2\tan^{-1}x\text{ if }|x|\leq{1}\\ \pi-2\tan^{-1}x\text{ if }|x|>{1}\text{ and }x>0\\ -\pi-2\tan^{-1}x\text{ if }|x|>{1}\text{ and }x<0 \end{cases} $$ $$ \int\sin^{-1}\frac{2x}{1+x^2}\,dx=\begin{cases}\int2\tan^{-1}x\,dx&\text{ if } |x|\leq{1}\\\int\pi\, dx-\int2\tan^{-1}x\,dx&\text{ if }|x|>{1}&\text{ and } x>0\\-\int\pi \,dx-\int2\tan^{-1}x\,dx&\text{ if }|x|>{1}&\text{ and } x<0\end{cases}=\begin{cases}\color{red}{2x\tan^{-1}x-\log(1+x^2)+C\text{ if } |x|\leq{1}}\\\pi x-2x\tan^{-1}x+\log(1+x^2)+C&\text{ if }|x|>{1}&\text{ and } x>0\\-\pi x-2x\tan^{-1}x+\log(1+x^2)+C&\text{ if }|x|>{1}&\text{ and } x<0\end{cases}$$

So don't we have two more cases for our solution rather than that is given in my reference, right ?

  • $\begingroup$ Are you asking why $\sin^{-1}\frac{2x}{1+x^2}=2\tan^{-1}x$? $\endgroup$ – A.Γ. May 15 '18 at 8:50
  • $\begingroup$ @A.Γ. i mean my reference seems to take only that. But, what about the other two cases ? $\endgroup$ – ss1729 May 15 '18 at 8:55

You're right; but it depends on what the full question is; if one is asked to compute $$ \int_{0}^{1}\arcsin\frac{2x}{1+x^2}\,dx $$ then just the antiderivative $2\arctan x$ is sufficient. Not if one wants to compute an integral involving points outside the interval $[-1,1]$.

Here's a shorter way to get at your result.

Consider $$ f(x)=\arcsin\frac{2x}{1+x^2} $$ Then $$ f'(x)=\frac{1}{\sqrt{1-\dfrac{4x^2}{(1+x^2)^2}}}\frac{2(1+x^2)-4x^2}{(1+x^2)^2} =\frac{1+x^2}{|1-x^2|}\frac{2(1-x^2)}{(1+x^2)^2} $$ hence $$ f'(x)=\begin{cases} \dfrac{2}{1+x^2} & x\in(-1,1) \\[4px] -\dfrac{2}{1+x^2} & x\in(-\infty,-1)\cup(1,\infty) \end{cases} $$ Therefore, knowing that $f(0)=0$, $$ f(x)=\begin{cases} -\pi-2\arctan x & x<-1 \\[4px] 2\arctan x & -1\le x\le 1 \\[4px] \pi-2\arctan x & x>1 \end{cases} $$

In order to find an antiderivative we can consider $$ \int\arctan x\,dx=x\arctan x-\int\frac{x}{1+x^2}\,dx =x\arctan x-\frac{1}{2}\log(1+x^2) $$ Thus an antiderivative of $f$ has the form $$ F(x)=\begin{cases} c_- -\pi x-2x\arctan x+\log(1+x^2) &\qquad x<-1 \\[4px] 2x\arctan x-\log(1+x^2) &\qquad -1\le x\le 1 \\[4px] c_+ +\pi x-2x\arctan x+\log(1+x^2) &\qquad x>1 \end{cases} $$ and you just need to determine $c_-$ and $c_+$ to ensure continuity at $-1$ and $1$.

The other antiderivatives differ from $F$ by a constant.

  • $\begingroup$ thanx. I like ur observation about the function from the derivative. thats something i never thought of, though i have seen it many times. $\endgroup$ – ss1729 May 16 '18 at 4:43

The "identity"

$$\arcsin\left(2x\over1+x^2\right)=2\arctan x$$

does not hold for all $x$. You can see this by comparing the ranges of the two sides. The arcsine function has $[-\pi/2,\pi/2]$ as its range, but twice the arctangent function has $(-\pi,\pi)$ as its range. In particular, if $x\gt1$, then $2\arctan x\gt\pi/2$, and likewise if $x\lt-1$ then $2\arctan x\lt-\pi/2$ (since $\arctan1=\pi/4$).

The correct identity is

$$\arcsin\left(2x\over1+x^2\right)= \begin{cases} \pi-2\arctan x\qquad\text{if }x\ge1\\ 2\arctan x\qquad\quad\text{ }\text{ if }-1\le x\le1\\ -\pi-2\arctan x\quad\text{ if }x\le-1 \end{cases}$$

(Note, I've intentionally overlapped the intervals at $x=\pm1$ to stress the agreement of $\pi-2\arctan1=2\arctan1$ and $2\arctan(-1)=-\pi-2\arctan(-1)$.) The OP's observations regarding the integral follow.


According to the standard tangent half-angle substitution \begin{align} & x=\tan\frac\theta 2 \\[8pt] & 2\arctan x = \theta \\[8pt] & \frac {2\,dx}{1+x^2} = d\theta \\[8pt] & dx = \sec^2\frac\theta 2 \,\,\frac{d\theta} 2 \\[8pt] & \frac{2x}{1+x^2} = \sin\theta \\[8pt] & \frac{1-x^2}{1+x^2} = \cos\theta \end{align} Thus we have $\theta = \arcsin\dfrac{2x}{1+x^2}.$ So \begin{align} & \int \arcsin\frac{2x}{1+x^2} \, dx = \int \theta \left( \sec^2\frac\theta 2 \,\, \frac{d\theta} 2 \right) = \int\theta \, dv = \theta v - \int v\,d\theta \\[10pt] = {} & \theta\tan\frac\theta 2 - \int \tan\frac\theta 2 \, d\theta = \theta\tan\frac\theta 2 +2\log\left|\cos\frac\theta 2\right| + C \\[10pt] = {} & \theta \tan \frac \theta 2 + \log\left|\frac 1 2 + \frac 1 2 \cos\theta \right| + C = \theta\tan\frac \theta 2 + \log\left| \frac 1 2 + \frac{1-x^2}{2(1+x^2)} \right| + C \\[10pt] = {} & 2x\arctan x - \log(1+x^2) + C \end{align}

  • 1
    $\begingroup$ It follows that $\arcsin\frac{2x}{1+x^2}=2\arctan x$, for all $x$, which is obviously false. $\endgroup$ – egreg May 16 '18 at 6:52
  • $\begingroup$ @egreg : It's true if $-1\le x\le1,$ so I guess some piecewise stuff needs to be added$\,\ldots\qquad$ $\endgroup$ – Michael Hardy May 16 '18 at 16:30

We know that $\tan(\theta/2) = \frac{\sin(\theta)}{1+\cos(\theta)}$ and $\cos(\theta) = \sqrt{1-\sin^2(\theta)}$. So, letting $x = \sin(\theta)$ $(\implies \theta = \arcsin(x))$ we have:

$\tan(\theta/2) = \frac{x}{1+\sqrt{1-x^2}} \implies \frac{\theta}{2} = \arctan\left(\frac{x}{1+\sqrt{1-x^2}}\right) \implies \arcsin(x) = 2\arctan\left(\frac{x}{1+\sqrt{1-x^2}}\right)$.

With that in hands, we just have to calculate $\arcsin\left(\frac{2x}{1+x^2}\right) = 2\arctan\left(\frac{\frac{2x}{1+x^2}}{1+\sqrt{1-\frac{4x^2}{1+2x^2+x^4}}}\right)$.

Now observe that $\frac{\frac{2x}{1+x^2}}{1+\sqrt{1-\frac{4x^2}{1+2x^2+x^4}}} = \frac{\frac{2x}{1+x^2}}{1+\sqrt{\frac{1-2x^2+x^4}{1+2x^2+x^4}}} = \frac{\frac{2x}{1+x^2}}{1+\frac{1-x^2}{1+x^2}} = \frac{\frac{2x}{1+x^2}}{\frac{2}{1+x²}} = x$. I thik this solve the equality you were struggling with.

  • 1
    $\begingroup$ It is true only for $x\in[-1\ 1]$ (otherwise $\arcsin x$ is not defined). Compare the graphs. $\endgroup$ – A.Γ. May 15 '18 at 11:13
  • $\begingroup$ For all $x \in \mathbb{R}$ we have $2x/(1+x^2) \in [-1,1]$, otherwise $2x/(1+x²) < -1 \implies 2x < -1-x^2 \implies 0 < -(1+x)^2$. Contradiction. Analogously we can't have $1 < 2x/(1+x^2) \implies 1+x^2 < 2x \implies (1-x)^2 < 0$. $\endgroup$ – Xablau123 May 15 '18 at 11:36
  • $\begingroup$ i'm sorry i dont get wht u r trying to say. my doubt wht was whether it has three cases for the solution ? $\endgroup$ – ss1729 May 15 '18 at 12:29
  • $\begingroup$ When you take your solution and derivate it, you'll have $2\arctan(x)$. What I showed is that actually $2\arctan(x) = \arcsin(\frac{2x}{1+x^2})$ for every $x \in \mathbb{R}$ and, by my previously comment, it's "well-defined". $\endgroup$ – Xablau123 May 15 '18 at 12:42
  • 1
    $\begingroup$ @Xablau123 ... and you will notice that it is not true if you look at their graphs in the link in my previous comment.Your mistake: when you take the square root you will get $|1-x^2|$. You forgot the absolute value there. $\endgroup$ – A.Γ. May 15 '18 at 13:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.